The Popo and Komikazer Illustration on Tokai Gas Lighter that can Influence Buyer Interest - Hardoyo, A B (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of the research is to find out the cartoon illustration of The Popo who collaboration with Komikazer which is placed on a Tokai gas lighter brand can increase purchase interest. The method used in this research is quantitative by describe the illustration who applied to gas lighter and conducting questionnaries about that illustration on a match to respondents to produce data to know the conclusion. The result obtained from the research is knowledge in form of placing illustration The Popo and Komikazer on a gas lighter can be increase interest in deciding to buy a gas lighter match and the message in an illustration can be important in increasing the interest of potential customers.